Exogenous Expression of Equine MHC Class I Molecules in Mice Increases Susceptibility to Equine Herpesvirus 1 Pulmonary Infection. Issue 5 (September 2019) - Minato, Erina; Aoshima, Keisuke; Kobayashi, Atsushi; Ohnishi, Naomi; Sasaki, Nobuya; Kimura, Takashi
Equine herpesvirus 1 (EHV-1) uses equine major histocompatibility complex class I (MHC class I) as an entry receptor. Exogenous expression of equine MHC class I genes in murine cell lines confers susceptibility to EHV-1 infection. To examine the in vivo role of equine MHC class I as an entry receptor for EHV-1, we generated transgenic (Tg) mice expressing equine MHC class I under the control of the CAG promoter. Equine MHC class I protein was expressed in the liver, spleen, lung, and brain of Tg mice, which was confirmed by Western blot. However, equine MHC class I antigen was only detected in bronchiolar epithelium and not in other tissues, using the immunofluorescence method employed in this study. Both Tg and wild-type (WT) mice developed pneumonia 3 days after intranasal infection with EHV-1. The bronchiolar epithelial cells of Tg mice showed more severe necrosis, compared with those in WT mice. In addition, the number of virus antigen-positive cells in the lungs was higher in Tg mice than in WT mice. These results suggest that exogenous expression of equine MHC class I renders mice more susceptible to EHV-1 infection.